Analisis Strategi Guru Sejarah Dalam Menanamkan Karakter Nasionalisme Pada Peserta Didik Kelas XI IPS SMA Santo Fransiskus Asisi Pontianak - Yosafat Kevin; Ika Rahmatika Chalimi; Haris Firmansyah (Journal on Education, 2024)
The role of parents and teachers is very important in shaping the character of students, especially nationalism character. Teachers have the task of instilling nationalism character in the learning process. This research used qualitative methods with descriptive form. The research subjects consisted of history teachers, and students. The data collection techniques used observation, interviews and documentation with the data collection tools are in the form of observation guidelines, interview guidelines and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of this research show that: (1) history teachers instill the character of nationalism in students by having students take part in flag ceremonies, using Indonesian language properly and correctly, and participate in singing national or mandatory songs. (2) The method of implementing strategies used by history teachers to su pport their strategy forms can be in the form of making lesson plans (RPP), using learning media, and through discussions. and (3) the obstacles encountered by history teachers in carrying out their forms of strategy can be from the use of the learning media used, the differences in character of each student, and the allocation of time. So, it can be concluded that the things that history teachers have done in learning can foster nationalist character in students.